Microsoft Office 2007 illustrated - David W. Beskeen (Thomson Course Technology, 2008)
Part of the Illustrated Series, this practical, easy to navigate book provides the essential knowledge of Microsoft Office 2007 you need to succeed in both the classroom and beyond